2019
DOI: 10.1002/jcp.27711
|View full text |Cite
|
Sign up to set email alerts
|

AZD8835 inhibits osteoclastogenesis and periodontitis‐induced alveolar bone loss in rats

Abstract: Chronic periodontitis (CP) is one of the most common oral diseases, which is characterized by the loss of connective tissue and alveolar bone in adults. AZD8835, a novel dual phosphoinositide‐3‐kinase (PI3K) inhibitor, is currently in phase 1 clinical evaluation to treat breast cancer. However, whether AZD8835 has any effect on teeth and alveolar bone health remains unclear. In the current study, we aimed to investigate the potential effect of AZD8835 in treating CP in vitro and in vivo. We found that AZD8835 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The Gram-negative anaerobic bacterium P. gingivalis has been considered the keystone pathogen in periodontitis ( 6 ). Recent findings have suggested P. gingivalis plays an essential role in systemic diseases, such as cardiovascular diseases, rheumatoid arthritis, diabetes, pregnancy problems, Alzheimer’s disease, and insulin resistance ( 35 38 ). Henceforth, it is imperative to form a deeper understanding of the mechanism of P. gingivalis in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…The Gram-negative anaerobic bacterium P. gingivalis has been considered the keystone pathogen in periodontitis ( 6 ). Recent findings have suggested P. gingivalis plays an essential role in systemic diseases, such as cardiovascular diseases, rheumatoid arthritis, diabetes, pregnancy problems, Alzheimer’s disease, and insulin resistance ( 35 38 ). Henceforth, it is imperative to form a deeper understanding of the mechanism of P. gingivalis in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…RANKL treatment facilitated the phosphorylation of GSK3β and induced its interaction and co-localization with heterogeneous nuclear ribonucleoprotein K (hnRNPK), leading to enhanced NFATc1 expression and osteoclast formation [ 42 , 43 ]. Inhibition of Akt by PI3K inhibitors results in deficient osteoclast formation and protects mice from osteolytic bone loss [ 44 , 45 ]. A previous study reported that Syap1 was induced by mTORC2 and facilitated the interaction between Syap1 and Akt1 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…BMMs were prepared for osteoclast culture as previously described [34]. Brie y, primary BMMs were isolated immediately from the femurs and tibias of C57BL/6 mice.…”
Section: Cell Culture and Animalsmentioning
confidence: 99%